2016
DOI: 10.1021/acs.biochem.6b00887
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Conformational States Dictate Selectivity toward the Native Substrate in a Substrate-Permissive Acyltransferase

Abstract: Hydroxycinnamoyl CoA: shikimate hydroxycinnamoyl transferase (HCT) is an essential acyltransferase that mediates flux through plant phenylpropanoid metabolism by catalyzing a reaction between p-coumaroyl CoA and shikimate, yet it also exhibits broad substrate permissiveness in vitro. How do enzymes like HCT avoid functional derailment by cellular metabolites that qualify as non-native substrates? Here, we combine X-ray crystallography and molecular dynamics to reveal distinct dynamic modes of HCT under native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 63 publications
9
106
0
Order By: Relevance
“…This theme is exemplified by the hydroxycinnamoyltransferases (HCTs), which play a role in phenylpropanoid biosynthesis [2326]. HCTs are involved in the conjugation of p -coumaroyl CoA to shikimate to form p -coumaroyl shikimate, and can be highly promiscuous [2326]. For example, the A. thaliana HCT (AtHCT) uses nine substrates besides the native substrate shikimate – some better than shikimate (Figure 2C) – to produce a diversity of products in vitro .…”
Section: Hydroxycinnamoyltransferases Illustrate How the Interface Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…This theme is exemplified by the hydroxycinnamoyltransferases (HCTs), which play a role in phenylpropanoid biosynthesis [2326]. HCTs are involved in the conjugation of p -coumaroyl CoA to shikimate to form p -coumaroyl shikimate, and can be highly promiscuous [2326]. For example, the A. thaliana HCT (AtHCT) uses nine substrates besides the native substrate shikimate – some better than shikimate (Figure 2C) – to produce a diversity of products in vitro .…”
Section: Hydroxycinnamoyltransferases Illustrate How the Interface Ofmentioning
confidence: 99%
“…Crystallography and molecular dynamics analysis of AtHCT highlighted two mechanisms by which HCT maintains its in vivo function while being such a promiscuous enzyme [26]. First, comparison of AtHCT apoenzyme:substrate crystal structure and molecular dynamics revealed that this enzyme undergoes a conformational change upon p -coumaroyl-CoA or p -coumaroylshikimate binding: this reduces the volume of the active site and induces changes in the position of residues involved in substrate binding and catalysis [26].…”
Section: Hydroxycinnamoyltransferases Illustrate How the Interface Ofmentioning
confidence: 99%
See 3 more Smart Citations